2015
DOI: 10.2216/15-30.1
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic antioxidant defences are transcriptionally regulated in Es524, a copper-tolerant strain of Ectocarpus siliculosus (Ectocarpales, Phaeophyceae)

Abstract: Previous investigations have revealed that Ectocarpus siliculosus strain Es524, isolated from a highly copper (Cu)-polluted location in Chile, displays higher activities of the antioxidant enzymes superoxide dismutase (SOD), ascorbate peroxidase (APX) and catalase (CAT) under Cu excess. This partly explains its enhanced tolerance compared with other E. siliculosus strains. However, the transcriptomic basis behind the activity of these antioxidant enzymes is still unknown. We have conducted laboratory experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…On the other hand, it could be hypothesised that gene repression under copper and combined MAPK inhibitors is caused by the low levels of intracellular copper detected in these treatments in Celis-Plá et al [1]. Indeed, it has been observed that the expression of the enzymes SOD, CAT, and APX had a positive correlation with levels of intracellular copper in the brown macroalga Ectocarpus siliculosus [5,39]. However, this explanation appears unlikely considering that the decline of antioxidant defences in treatments with copper and combined MAPK inhibitors most of the time reached levels even below control conditions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it could be hypothesised that gene repression under copper and combined MAPK inhibitors is caused by the low levels of intracellular copper detected in these treatments in Celis-Plá et al [1]. Indeed, it has been observed that the expression of the enzymes SOD, CAT, and APX had a positive correlation with levels of intracellular copper in the brown macroalga Ectocarpus siliculosus [5,39]. However, this explanation appears unlikely considering that the decline of antioxidant defences in treatments with copper and combined MAPK inhibitors most of the time reached levels even below control conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The primers (forward and reverse) were designed from NIH GenBank using Primer Output 3 software (Table 2 ). Acanthamoeba actin related protein 2 (ARP2) is used as housekeeping gene in this study [ 42 , 43 ]. Quantitative polymerase chain reactions were performed using MyiQ cycler (Bio-Rad, Hercules, CA, USA) with iQ™ SYBR® Green Supermix (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, some algal species have been reported to display increased tolerance to copper due to a constant exposure to elevated copper concentrations. [48,60,61] Therefore, the use of unrealistically high copper concentrations in ecotoxicological studies can also have physiological relevance for the toxicity threshold of copper-tolerant marine algal species. [36] …”
Section: Discussionmentioning
confidence: 99%